Diffusion mass transfer in ionic materials under intense electron irradiation; IOP Conference Series: Materials Science and Engineering; Vol. 168 : Radiation-Thermal Effects and Processes in Inorganic Materials (RTEP2016) - Bochkarev I. G.; Gyngazov (Ghyngazov) S. A. Sergey Anatolievich; Frangulyan (Franguljyan) Т. S. Tamara Semenovna; Petrova A. B. Anna Borisovna; Chernyavski (Chernyavskiy) A. V. Aleksandr Viktorovich (Adjacent to the main theme of the conference issues, 2017)
Title screen